Composite coating based on modified hydrogenated bisphenol A epoxy resin and preparation method thereof

By modifying hydrogenated bisphenol A type epoxy resin, a complex crosslinking network is formed, which solves the problems of slow curing speed, insufficient hardness, poor chemical resistance and insufficient weather resistance in industrial applications of water-based epoxy resin floors. , significantly improves the impact resistance, wear resistance and acid and alkali resistance of composite coatings.

CN119463648AInactive Publication Date: 2025-02-18SHANGHAI RESIN FACTORY

Patent Information

Application Number
CN202510047332.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In actual applications, water-based epoxy resin floors face problems such as slow curing speed, insufficient surface hardness, poor chemical resistance and insufficient weather resistance, which affects their application in industrial floors.

Method used

Modification of hydrogenated bisphenol A type epoxy resin includes reacting with acrylic acid and fluorine-containing carboxylic acid to form ester bonds, and forming a complex crosslinking network through grafting reaction and acid anhydride reaction, improving the impact resistance of composite coatings, Wear resistance and acid and alkali resistance.

Benefits of technology

The modified composite coating has improved impact resistance at room temperature, and exhibits better durability and corrosion resistance under changing temperature conditions and in the face of acid and alkali environments, extending the service life of industrial floors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings, and particularly relates to a composite coating based on modified hydrogenated bisphenol A epoxy resin and a preparation method thereof, the composite coating comprises the following components in parts by weight: a component A and a component B, the component A is prepared from the following components in parts by weight: 48 to 52 parts of amine curing agent, 25 to 30 parts of modified filler, 0.4 to 0.9 part of flatting agent and 0.2 to 0.6 part of defoaming agent; and the component B comprises the following components in parts by weight: 65-70 parts of hydrogenated bisphenol A epoxy resin, 15-20 parts of auxiliary resin and 1-3 parts of an emulsifier. The prepared composite coating is excellent in comprehensive performance and suitable for preparing industrial terraces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a composite coating based on modified hydrogenated bisphenol A type epoxy resin and a preparation method thereof. Background Art

[0002] Industrial flooring refers to the floors used in industrial and commercial places such as factories, warehouses, logistics centers, and parking lots. These floors need to have high strength, wear resistance, chemical corrosion resistance, and easy cleaning to meet specific working environment requirements.

[0003] As an environmentally friendly material, waterborne epoxy resin has been widely used in industrial flooring due to its low VOC (volatile organic compound) emissions and environmental friendliness. At present, the waterborne epoxy resin flooring on the market is mainly prepared and constructed by hydrogenated bisphenol A epoxy resin (128 epoxy resin), curing agent, and various additives. However, compared with traditional solvent-based epoxy resins, waterborne epoxy resins still face some technical challenges in practical applications: 1. Slow curing speed: The curing speed of waterborne epoxy resins is usually slower than that of solvent-based epoxy resins, especially in low temperature or high humidity environments, which may lead to a longer construction period and affect the construction progress. 2. Insufficient surface hardness: The cross-linking density of waterborne epoxy resins is low, resulting in its surface hardness may not be as good as that of solvent-based epoxy resins, especially in the early stages, and it is prone to scratches or wear. 3. Poor chemical resistance: Although waterborne epoxy resins have a certain ability to resist chemical corrosion, their chemical resistance may not be as good as that of solvent-based epoxy resins under the action of certain strong acids, strong alkalis or organic solvents, and they are prone to discoloration, softening or peeling. 4. Insufficient weather resistance: When used outdoors, water-based epoxy resins may be affected by ultraviolet rays, temperature changes, and chemicals, causing the coating to age, chalk, or lose gloss.

[0004] Chinese patent CN202011629160.4 provides a water-based epoxy resin coating, which improves the wear resistance, elasticity, hardness, glossiness, bright surface and other properties of the coating by adding powders consisting of latex powder, quartz powder, wax powder, titanium dioxide and sulfuric acid to the components. Although these additives can improve the physical properties, they will weaken the chemical resistance of the coating, especially the resistance to strong acids, strong alkalis and organic solvents, affecting its application in industrial floors.

[0005] Therefore, there is an urgent need for a composite coating based on modified hydrogenated bisphenol A epoxy resin and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a composite coating based on modified hydrogenated bisphenol A type epoxy resin and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: A composite coating based on modified hydrogenated bisphenol A epoxy resin, comprising the following components in parts by weight: component A and component B; the component A comprises, by parts by weight: 48-52 parts of an amine curing agent, 25-30 parts of a modified filler, 0.4-0.9 parts of a leveling agent, and 0.2-0.6 parts of a defoaming agent; the component B comprises, by parts by weight: 65-70 parts of hydrogenated bisphenol A epoxy resin, 15-20 parts of an auxiliary resin, and 1-3 parts of an emulsifier; The preparation method of the modified hydrogenated bisphenol A type epoxy resin comprises the following steps: (1) 20-25 parts by weight of epichlorohydrin, 15-20 parts by weight of hydrogenated bisphenol A, and 0.1-0.2 parts by weight of boron trifluoride etherate are mixed, the temperature is raised to 70-90° C. for reaction for 2-5 hours, and then 30-40 parts by weight of methyl isobutyl ketone and 20-25 parts by weight of sodium hydroxide are added, the temperature is raised to 60-65° C. for reaction for 2-5 hours to obtain an epoxy resin precursor; (2) extracting the epoxy resin precursor prepared in step (1) with deionized water for 2-3 times to obtain an extraction product, heating the extraction product to 80-85° C., adding 3-5 parts by weight of sodium hydroxide aqueous solution, and reacting at 80-85° C. for 5-7 hours to obtain a reaction product; (3) extracting the reaction product with toluene 2-3 times and deionized water 2-3 times to obtain a hydrogenated bisphenol A epoxy resin; (4) 28-32 parts by weight of hydrogenated bisphenol A epoxy resin, 0.15-0.17 parts by weight of p-hydroxyanisole, and 0.6-0.8 parts by weight of 2-methylaminopyridine are mixed, the temperature is raised to 90-95° C., 5.5-6.5 parts by weight of acrylic acid are added dropwise, and then 55-58 parts by weight of fluorinated carboxylic acid are added dropwise, the temperature is raised to 110-115° C., and the reaction is carried out for 3.5-4 hours to obtain a grafted hydrogenated bisphenol A epoxy resin; (5) 36 parts by weight of grafted hydrogenated bisphenol A epoxy resin and 8-10 parts by weight of acid anhydride are mixed, stirred at 90-95°C for 3-4 hours, 5.5-6.5 parts by weight of triethylamine and 50-55 parts by weight of deionized water are added, the temperature is raised to 50-55°C, and the reaction is carried out for 1-2 hours to obtain a modified hydrogenated bisphenol A epoxy resin.

[0008] In factories, warehouses, logistics centers and other places, heavy equipment, forklifts, pallets and the like are often moved or operated on the ground, so industrial floors have high requirements for the impact resistance of coatings. The present invention can improve the impact resistance of composite coatings at room temperature by modifying the prepared hydrogenated bisphenol A epoxy resin. The present invention first prepares hydrogenated bisphenol A epoxy resin, and then the epoxy groups in the hydrogenated bisphenol A epoxy resin undergo a ring-opening reaction with the carboxyl groups in acrylic acid and fluorinated carboxylic acid under the action of 2-methylaminopyridine catalyst to generate ester bonds, and finally the hydroxyl groups on the grafted hydrogenated bisphenol A epoxy resin react with the anhydride. Through a series of reactions, the composite coating can have a complex cross-linked network, thereby improving the impact resistance of the composite coating.

[0009] Furthermore, the fluorine-containing carboxylic acid is a mixture of tridecafluoroheptanoic acid, trifluoroacetic acid and heptafluorobutyric acid in a weight ratio of 1: (1.2-1.4): (0.5-0.7).

[0010] Furthermore, the acid anhydride is a mixture of maleic anhydride, succinic anhydride and methyltetrahydrophthalic anhydride in a weight ratio of 1: (0.3-0.5): (1.5-1.7).

[0011] Furthermore, the preparation method of the modified filler comprises the following steps: (1) mixing silicon dioxide, double-walled carbon nanotubes and lanthanum oxide to obtain a mixed filler; (2) Add 10 parts by weight of mixed filler and 23-25 ​​parts by weight of polyethylene glycol to 160-180 parts by weight of ethanol aqueous solution, mix and stir for 15-20 minutes; continue to drop 2-3 parts by weight of methacrylic acid oxypropylmethyldimethoxysilane, 3-5 parts by weight of tin dichloride and 10 parts by weight of methacrylate glycidyl ester, react at 40-50° C. for 40-60 minutes; centrifuge, wash, and dry to obtain a modified filler.

[0012] Furthermore, the weight ratio of silicon dioxide, double-walled carbon nanotubes and lanthanum oxide is 1:(1.2-1.4):(0.5-0.7).

[0013] Furthermore, the average particle size of silicon dioxide is 10 nm and the average specific surface area is 380 m 2 / g; double-walled carbon nanotubes have a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​380m 2 / g; the particle size of lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

[0014] The present invention improves the wear resistance of the composite coating by adding a modified filler prepared by mixing a specific type of mixed filler in a ratio. By modifying the mixed filler, a functional group having better compatibility with the matrix material is introduced on the surface of the filler, which can improve the compatibility of the filler with other raw materials, thereby improving the wear resistance of the composite coating.

[0015] Moreover, when using fluorinated carboxylic acids, acid anhydrides and fillers with specific parameters in a specific ratio, the impact resistance of the composite coating under variable temperature conditions can be improved, and the service life of industrial floors in northern regions can be extended.

[0016] Furthermore, the auxiliary resin includes a water-based polyester resin, a water-based acrylic resin and a water-based phenoxy resin in a weight ratio of 1: (1.2-1.5): (0.5-0.8).

[0017] In many industrial environments, the ground is frequently exposed to various acids, alkalis and other chemicals, which may cause corrosion, softening, discoloration or peeling of ordinary ground materials, affecting the service life and safety of the ground. The present invention can improve the acid and alkali resistance of the composite coating by adding auxiliary resins to the composite coating. By introducing water-based polyester resins, water-based acrylic resins and water-based phenoxy resins, a more complex cross-linked network can be formed in the coating; different types of resins can further enhance the intermolecular binding force through interaction, making the coating more dense and stable.

[0018] Furthermore, the amine curing agent is diethylenetriamine.

[0019] Furthermore, the emulsifier is selected from one of Span 20, Span 40 or Tween 60.

[0020] The present invention provides a method for preparing a composite coating based on modified hydrogenated bisphenol A epoxy resin, comprising the following steps: uniformly mixing an amine curing agent, a modified filler, a leveling agent and a defoaming agent to obtain component A; and uniformly mixing hydrogenated bisphenol A epoxy resin, an auxiliary resin and an emulsifier to obtain component B.

[0021] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention can improve the impact resistance of the composite coating at room temperature by modifying the prepared hydrogenated bisphenol A epoxy resin.

[0022] 2. The present invention can improve the wear resistance of the composite coating by adding a modified filler prepared by mixing fillers of a specific type and ratio into the composite coating.

[0023] 3. When a fluorinated carboxylic acid, anhydride and filler with specific parameters are used in the system of the present invention, the impact resistance of the composite coating under variable temperature conditions can be improved.

[0024] 4. The present invention can improve the acid and alkali resistance of the composite coating by adding auxiliary resin into the composite coating. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The raw materials used in the following examples of the present invention are all commercially available products: Water-based phenoxy resin, brand: Huntsman, model: PHENOXY PKHW-35.

[0027] Waterborne polyurethane, Guangdong Xidun New Material Technology Co., Ltd., model SEAPUR 50W06.

[0028] Water-based acrylic resin, Guangdong Dongdun New Material Technology Co., Ltd., model SEACRYL 11K37.

[0029] Sipang 20, Haian Petrochemical Plant, Jiangsu Province, brand Haishihua.

[0030] Tridecafluoroheptanoic acid, CAS number: 375-85-9.

[0031] Methyltetrahydrophthalic anhydride, CAS number: 11070-44-3.

[0032] Methacrylic acid oxypropylmethyldimethoxysilane, CAS No. 14513-34-9, Hangzhou Heyu Technology Co., Ltd.

[0033] Polyethylene glycol, Hai'an Petrochemical Plant, Jiangsu Province, specification PEG200ML.

[0034] Example 1 This embodiment provides a composite coating based on modified hydrogenated bisphenol A epoxy resin, comprising the following components in parts by weight: component A and component B; the component A comprises, by weight: 50 parts of an amine curing agent, 27 parts of a modified filler, 0.6 parts of a leveling agent, and 0.4 parts of a defoaming agent; the component B comprises, by weight: 67 parts of hydrogenated bisphenol A epoxy resin, 18 parts of an auxiliary resin, and 2 parts of an emulsifier; The auxiliary resin includes a water-based polyester resin, a water-based acrylic resin and a water-based phenoxy resin in a weight ratio of 1:1.4:0.7.

[0035] The amine curing agent is diethylenetriamine. The emulsifier is Span 20. The leveling agent is TWIN-4100 leveling agent, and the defoaming agent is TEGO 901W defoaming agent.

[0036] The preparation method of the modified hydrogenated bisphenol A type epoxy resin comprises the following steps: (1) 22 parts by weight of epichlorohydrin, 17 parts by weight of hydrogenated bisphenol A, and 0.15 parts by weight of boron trifluoride etherate were mixed, the temperature was raised to 80° C. and reacted for 4 hours, and then 35 parts by weight of methyl isobutyl ketone and 22 parts by weight of sodium hydroxide were added, the temperature was raised to 62° C. and reacted for 3 hours to obtain an epoxy resin precursor; (2) The epoxy resin precursor prepared in step (1) was extracted three times with 155 parts by weight of deionized water to obtain an extraction product, the extraction product was heated to 82° C., 4 parts by weight of a 32 wt% sodium hydroxide aqueous solution was added, and the reaction was kept at 82° C. for 6 hours to obtain a reaction product; (3) extracting the reaction product with 56 parts by weight of toluene for three times and 76 parts by weight of deionized water for three times to obtain a hydrogenated bisphenol A epoxy resin; (4) 30 parts by weight of hydrogenated bisphenol A epoxy resin, 0.16 parts by weight of p-hydroxyanisole and 0.7 parts by weight of 2-methylaminopyridine were mixed, the temperature was raised to 92° C., 6 parts by weight of acrylic acid were added dropwise over a period of 0.6 h, and then 57 parts by weight of fluorinated carboxylic acid were added dropwise over a period of 1.2 h. The temperature was raised to 112° C. and the reaction was carried out for 3.7 h to obtain a grafted hydrogenated bisphenol A epoxy resin; (5) 36 parts by weight of grafted hydrogenated bisphenol A epoxy resin and 9 parts by weight of acid anhydride were mixed, stirred at 92° C. for 3.5 hours, 6 parts by weight of triethylamine and 52 parts by weight of deionized water were added, the temperature was raised to 52° C., and the reaction was carried out for 1.5 hours to obtain modified hydrogenated bisphenol A epoxy resin.

[0037] The fluorine-containing carboxylic acid is a mixture of tridecafluoroheptanoic acid, trifluoroacetic acid and heptafluorobutyric acid in a weight ratio of 1:1.3:0.6.

[0038] The acid anhydride is a mixture of maleic anhydride, succinic anhydride and methyltetrahydrophthalic anhydride in a weight ratio of 1:0.4:1.6.

[0039] The preparation method of the modified filler comprises the following steps: (1) mixing silicon dioxide, double-walled carbon nanotubes and lanthanum oxide in a weight ratio of 1:1.3:0.6 to obtain a mixed filler; (2) Add 10 parts by weight of mixed filler and 24 parts by weight of polyethylene glycol to 170 parts by weight of 57% (v / v) ethanol aqueous solution, mix and stir for 17 minutes; continue to drop 2.4 parts by weight of methacrylic acid oxypropylmethyldimethoxysilane, 4 parts by weight of tin dichloride and 10 parts by weight of methacrylate glycidyl ester, react at 45°C for 50 minutes; centrifuge, wash with deionized water three times, and dry to obtain a modified filler.

[0040] The average particle size of silica is 10 nm and the average specific surface area is 380 m 2 / g, Jinlei Technology, JL-SiO2-N10; double-walled carbon nanotubes with a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​380m 2 / g. Purchased from Xianfeng Nano. Lanthanum oxide has a particle size of 30nm-50nm and a specific surface area of ​​30-50m 2 / g. Purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0041] The preparation method of the composite coating based on modified hydrogenated bisphenol A epoxy resin comprises the following steps: uniformly mixing an amine curing agent, a modified filler, a leveling agent and a defoaming agent to obtain component A; and uniformly mixing hydrogenated bisphenol A epoxy resin, an auxiliary resin and an emulsifier to obtain component B.

[0042] Example 2 This embodiment provides a composite coating based on modified hydrogenated bisphenol A epoxy resin, comprising the following components in parts by weight: component A and component B; the component A comprises, in parts by weight: 48 parts of an amine curing agent, 30 parts of a modified filler, 0.4 parts of a leveling agent, and 0.6 parts of a defoaming agent; the component B comprises, in parts by weight: 65 parts of hydrogenated bisphenol A epoxy resin, 20 parts of an auxiliary resin, and 1 part of an emulsifier; The auxiliary resin includes a water-based polyester resin, a water-based acrylic resin and a water-based phenoxy resin in a weight ratio of 1:1.2:0.8.

[0043] The amine curing agent is diethylenetriamine, the emulsifier is Tween 60, the leveling agent is TWIN-4100 leveling agent, and the defoaming agent is TEGO 901W defoaming agent.

[0044] The preparation method of the modified hydrogenated bisphenol A type epoxy resin comprises the following steps: (1) 20 parts by weight of epichlorohydrin, 20 parts by weight of hydrogenated bisphenol A, and 0.1 parts by weight of boron trifluoride etherate were mixed, the mixture was heated to 90° C. and reacted for 2 hours, and then 40 parts by weight of methyl isobutyl ketone and 20 parts by weight of sodium hydroxide were added, the mixture was heated to 65° C. and reacted for 2 hours to obtain an epoxy resin precursor; (2) The epoxy resin precursor prepared in step (1) was extracted twice with 160 parts by weight of deionized water to obtain an extraction product, the extraction product was heated to 85° C., 3 parts by weight of a 35 wt% sodium hydroxide aqueous solution was added, and the reaction was kept at 80° C. for 7 hours to obtain a reaction product; (3) extracting the reaction product with 50 parts by weight of toluene for 3 times and 70 parts by weight of deionized water for 3 times to obtain a hydrogenated bisphenol A epoxy resin; (4) 28 parts by weight of hydrogenated bisphenol A epoxy resin, 0.17 parts by weight of p-hydroxyanisole, and 0.6 parts by weight of 2-methylaminopyridine were mixed, the temperature was raised to 95° C., 5.5 parts by weight of acrylic acid were added dropwise over a period of 0.7 h, and then 58 parts by weight of fluorinated carboxylic acid were added dropwise over a period of 1 h. The temperature was raised to 115° C. and the reaction was carried out for 3.5 h to obtain a grafted hydrogenated bisphenol A epoxy resin; (5) 36 parts by weight of grafted hydrogenated bisphenol A epoxy resin and 10 parts by weight of acid anhydride were mixed, stirred at 90° C. for 4 h, 5.5 parts by weight of triethylamine and 55 parts by weight of deionized water were added, the temperature was raised to 50° C., and the reaction was carried out for 2 h to obtain a modified hydrogenated bisphenol A epoxy resin.

[0045] The fluorine-containing carboxylic acid is a mixture of tridecafluoroheptanoic acid, trifluoroacetic acid and heptafluorobutyric acid in a weight ratio of 1:1.4:0.5.

[0046] The acid anhydride is a mixture of maleic anhydride, succinic anhydride and methyltetrahydrophthalic anhydride in a weight ratio of 1:0.5:1.5.

[0047] The preparation method of the modified filler comprises the following steps: (1) mixing silicon dioxide, double-walled carbon nanotubes and lanthanum oxide in a weight ratio of 1:1.2:0.7 to obtain a mixed filler; (2) Add 10 parts by weight of mixed filler and 25 parts by weight of polyethylene glycol to 180 parts by weight of 55% (v / v) ethanol aqueous solution, mix and stir for 20 minutes; continue to drop 3 parts by weight of methacrylic acid oxypropylmethyldimethoxysilane, 3 parts by weight of tin dichloride and 10 parts by weight of methacrylate glycidyl ester, react at 50°C for 40 minutes; centrifuge, wash with deionized water 3 times, and dry to obtain a modified filler.

[0048] The average particle size of silica is 10 nm and the average specific surface area is 380 m 2 / g, Jinlei Technology, JL-SiO2-N10; double-walled carbon nanotubes with a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​380m 2 / g. Purchased from Xianfeng Nano. Lanthanum oxide has a particle size of 30nm-50nm and a specific surface area of ​​30-50m 2 / g. Purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0049] The preparation method of the composite coating based on modified hydrogenated bisphenol A epoxy resin comprises the following steps: uniformly mixing an amine curing agent, a modified filler, a leveling agent and a defoaming agent to obtain component A; and uniformly mixing hydrogenated bisphenol A epoxy resin, an auxiliary resin and an emulsifier to obtain component B.

[0050] Comparative Example 1 The difference between this comparative example and Example 1 is that the modified hydrogenated bisphenol A epoxy resin is replaced by hydrogenated bisphenol A epoxy resin.

[0051] The preparation method of the hydrogenated bisphenol A type epoxy resin comprises the following steps: (1) 22 parts by weight of epichlorohydrin, 17 parts by weight of hydrogenated bisphenol A, and 0.15 parts by weight of boron trifluoride etherate were mixed, the temperature was raised to 80° C. and reacted for 4 hours, and then 35 parts by weight of methyl isobutyl ketone and 22 parts by weight of sodium hydroxide were added, the temperature was raised to 62° C. and reacted for 3 hours to obtain an epoxy resin precursor; (2) The epoxy resin precursor prepared in step (1) was extracted three times with 155 parts by weight of deionized water to obtain an extraction product, the extraction product was heated to 82° C., 4 parts by weight of a 32 wt% sodium hydroxide aqueous solution was added, and the reaction was kept at 82° C. for 6 hours to obtain a reaction product; (3) extracting the reaction product with 56 parts by weight of toluene for three times and 76 parts by weight of deionized water for three times to obtain a hydrogenated bisphenol A epoxy resin; Comparative Example 2 The difference between this comparative example and Example 1 is that: the fluorine-containing carboxylic acid is a mixture of tridecafluoroheptanoic acid, trifluoroacetic acid and heptafluorobutyric acid in a weight ratio of 1:1:1. The acid anhydride is a mixture of maleic anhydride, succinic anhydride and methyltetrahydrophthalic anhydride in a weight ratio of 1:1:1.

[0052] Comparative Example 3 The difference between this comparative example and Example 1 is that silicon dioxide, double-walled carbon nanotubes and lanthanum oxide are mixed in a weight ratio of 1:1:1 to obtain a mixed filler.

[0053] Comparative Example 4 The difference between this comparative example and Example 1 is that the average particle size of silicon dioxide is 20 nm and the average specific surface area is 240 m 2 / g, Jinlei Technology, JL-SiO2-N20. Double-walled carbon nanotubes have a diameter of 3-6nm, a length of 1-4μm, and a specific surface area of ​​210m 2 / g. Purchased from Xianfeng Nano. Lanthanum oxide has a particle size of 1μm-5μm and a specific surface area of ​​1-10m 2 / g. Purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0054] Comparative Example 5 The difference between this comparative example and Example 1 is that the auxiliary resin includes an aqueous polyester resin, an aqueous acrylic resin and an aqueous phenoxy resin in a weight ratio of 1:1:1.

[0055] Comparative Example 6 The difference between this comparative example and Example 1 is that the auxiliary resin is only water-based acrylic resin. Water-based acrylic resin, Guangdong Xidun New Material Technology Co., Ltd., model SEACRYL 11K37.

[0056] Performance Testing The performance tests were performed on the composite coatings prepared in Examples 1-2 and Comparative Examples 1-6.

[0057] 1. Refer to GB / T 22374-2018, test conditions: 750g / 500r, to measure the wear resistance; 2. Refer to GB / T 6739-2022, pencil method to determine the hardness of the paint film; 3. Refer to HG / T 4759-2014 to measure the impact resistance at room temperature (25°C). At the same time, place the sample at 4°C, 25°C and 45°C for 8 hours respectively as one cycle, for a total of 30 cycles, and then refer to HG / T 4759-2014 to measure the impact resistance under variable temperature conditions.

[0058] 4. Acid and alkali resistance shall be measured according to HG / T 4759-2014. If there is no blistering, cracking, peeling or powdering, it shall be qualified; if there is any one or more of blistering, cracking, peeling or powdering, it shall be unqualified.

[0059] The results are shown in Table 1.

[0060]

[0061] From the above performance test results, it can be seen that the composite coatings of Examples 1-2 have excellent wear resistance, impact resistance and acid and alkali resistance, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the raw materials.

[0062] However, the comparative examples are significantly inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the prepared hydrogenated bisphenol A epoxy resin is not modified, and the impact resistance of the composite coating at room temperature decreases. The composition of the mixed filler in comparative example 3 is different, and the wear resistance of the composite coating decreases. In comparative example 2, the ratio of fluorinated carboxylic acid and acid anhydride is changed, and in comparative example 4, the filler parameters are changed, and the impact resistance of the composite coating under variable temperature conditions decreases. The composition of the auxiliary resins in comparative examples 5 and 6 is different, and the acid and alkali resistance of the composite coating decreases. The above experimental results further demonstrate the importance of the technical solution defined in the present invention for its technical effect.

[0063] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite coating based on modified hydrogenated bisphenol A epoxy resin, characterized in that: The invention comprises the following components in parts by weight: component A and component B; the component A comprises, in parts by weight: 48-52 parts of an amine curing agent, 25-30 parts of a modified filler, 0.4-0.9 parts of a leveling agent and 0.2-0.6 parts of a defoaming agent; the component B comprises, in parts by weight: 65-70 parts of a hydrogenated bisphenol A epoxy resin, 15-20 parts of an auxiliary resin and 1-3 parts of an emulsifier; The preparation method of the modified hydrogenated bisphenol A type epoxy resin comprises the following steps: (1) 20-25 parts by weight of epichlorohydrin, 15-20 parts by weight of hydrogenated bisphenol A, and 0.1-0.2 parts by weight of boron trifluoride etherate are mixed, the temperature is raised to 70-90° C. for reaction for 2-5 hours, and then 30-40 parts by weight of methyl isobutyl ketone and 20-25 parts by weight of sodium hydroxide are added, the temperature is raised to 60-65° C. for reaction for 2-5 hours to obtain an epoxy resin precursor; (2) extracting the epoxy resin precursor prepared in step (1) with deionized water to obtain an extraction product, heating the extraction product to 80-85° C., adding 3-5 parts by weight of sodium hydroxide aqueous solution, and reacting at 80-85° C. for 5-7 hours to obtain a reaction product; (3) extracting the reaction product with toluene and deionized water in sequence to obtain a hydrogenated bisphenol A epoxy resin; (4) 28-32 parts by weight of hydrogenated bisphenol A epoxy resin, 0.15-0.17 parts by weight of p-hydroxyanisole, and 0.6-0.8 parts by weight of 2-methylaminopyridine are mixed, the temperature is raised to 90-95° C., 5.5-6.5 parts by weight of acrylic acid are added dropwise, and then 55-58 parts by weight of fluorinated carboxylic acid are added dropwise, the temperature is raised to 110-115° C., and the reaction is carried out for 3.5-4 hours to obtain a grafted hydrogenated bisphenol A epoxy resin; (5) 36 parts by weight of grafted hydrogenated bisphenol A epoxy resin and 8-10 parts by weight of acid anhydride are mixed, stirred at 90-95° C. for 3-4 hours, 5.5-6.5 parts by weight of triethylamine and 50-55 parts by weight of deionized water are added, the temperature is raised to 50-55° C., and the reaction is carried out for 1-2 hours to obtain a modified hydrogenated bisphenol A epoxy resin; The fluorinated carboxylic acid is a mixture of tridecafluoroheptanoic acid, trifluoroacetic acid and heptafluorobutyric acid in a weight ratio of 1: (1.2-1.4): (0.5-0.7); The acid anhydride is a mixture of maleic anhydride, succinic anhydride and methyltetrahydrophthalic anhydride in a weight ratio of 1: (0.3-0.5): (1.5-1.7); The preparation method of the modified filler comprises the following steps: (1) mixing silicon dioxide, double-walled carbon nanotubes and lanthanum oxide to obtain a mixed filler; (2) adding 10 parts by weight of mixed filler and 23-25 ​​parts by weight of polyethylene glycol to an ethanol aqueous solution, mixing and stirring for 15-20 minutes; continuing to dropwise add 2-3 parts by weight of methacrylic acid oxypropylmethyldimethoxysilane, 3-5 parts by weight of tin dichloride and 10 parts by weight of methacrylate glycidyl ester, reacting at 40-50° C. for 40-60 minutes; centrifuging, washing, and drying to obtain a modified filler; The weight ratio of silicon dioxide, double-walled carbon nanotubes and lanthanum oxide is 1:(1.2-1.4):(0.5-0.7); The average particle size of silica is 10 nm and the average specific surface area is 380 m 2 / g; double-walled carbon nanotubes have a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​380m 2 / g; the particle size of lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g; The auxiliary resin includes a water-based polyester resin, a water-based acrylic resin and a water-based phenoxy resin in a weight ratio of 1: (1.2-1.5): (0.5-0.8).

2. The composite coating based on modified hydrogenated bisphenol A type epoxy resin according to claim 1, characterized in that: The amine curing agent is diethylenetriamine.

3. The composite coating based on modified hydrogenated bisphenol A type epoxy resin according to claim 1, characterized in that: The emulsifier is selected from one of Span 20, Span 40 or Tween 60.

4. A method for preparing a composite coating based on modified hydrogenated bisphenol A epoxy resin according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: uniformly mixing an amine curing agent, a modified filler, a leveling agent and a defoaming agent to obtain a component A; and uniformly mixing a hydrogenated bisphenol A type epoxy resin, an auxiliary resin and an emulsifier to obtain a component B.

Citation Information

Patent Citations

  • Waterborne epoxy resin coatings, waterborne epoxy resin coatings, flooring and their preparation methods

    CN112778872B

  • Preparation method for hydrogenated bisphenol A epoxy resin

    CN104193961A

  • Method for preparing modified nanosilicon dioxide

    CN104860320A

  • Baking-type aqueous organic silicon fluorine-containing polymer paint, coating, and method for manufacturing the same

    CN107083143A

  • Epoxy terrace material and preparation method thereof

    CN108864886A

Cited By

  • Epoxy resin composite coating and preparation method thereof

    CN120590840A

  • An epoxy resin composite coating and a method for preparing the same

    CN120590840B